Grading of distal colorectal adenomas as predictors for proximal colonic neoplasia and choice of endoscope in population screening: experience from the Norwegian Colorectal Cancer Prevention study (NORCCAP). (1st March 2003) - Gondal, G; Grotmol, T; Hofstad, B; Bretthauer, M; Eide, T J; Hoff, G
Abstract : Background and aims: The purpose of this study was to evaluate the utility of easily measured clinical variables at flexible sigmoidoscopy (FS) screening that might predict a proximal advanced neoplasm (PAN). Methods: We studied 1833 subjects with biopsy verified adenomas at FS who subsequently underwent full colonoscopy. Results: A total of 387 (21%) subjects had proximal colonic neoplasms (PCN) and 85 (5%) had PAN. In univariate comparison, the risk of PAN increased more than threefold in the presence of a distal adenoma measuring either ≥10 mm in diameter or containing villous components. Multiplicity of distal adenomas, severe dysplasia, or age ≥60 years increased the risk of PAN more than twofold. In the multivariate model, the presence of a distal adenoma ≥10 mm, villousness, and multiplicity maintained their significance as predictive variables for increased risk of proximal neoplasms, whereas sex and severe dysplasia lost their significance. By recommending colonoscopy only to individuals with multiple (>1) adenomas or any high risk adenoma at FS, we would have reduced the number of colonoscopies by 1209 (66%) but would have missed 32 (38%) participants with PAN and 217 (56%) with PCN. By using a 60 cm endoscope instead of an ordinary colonoscope at FS, nine (2%) participants with advanced neoplasms, including three patients with cancer, would have been missed. Conclusion: The present study supports the concept of defining "any adenoma" as a positive FS, qualifying for colonoscopy. We recommend the use of an ordinary colonoscope instead of a 60 cm sigmoidoscope for FS screening examinations.